Circulating miRNA biomarkers in Metabolic Syndrome and clinical obesity and their link with triple negative breast cancer - O'Neill, Sadhbh (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2017)
Metabolic syndrome (MetS), which is a spectrum of conditions including abdominal obesity, dyslipidemia, hypertension, and insulin resistance are increasing in prevalence globally and lead to an increased risk of cardiovascular disease. Type 2 diabetes mellitus and cancer. The focus of this project was to seek blood-based biomarkers for MetS, in the form of miRNAs, extracellular vesicles and proteins (i.e. neuromedin U and interleukin 6). Additionally, triple negative breast cancer (TNBC) risk has been epidemiologically linked to MetS and obesity. This association was addressed by investigating the metabolic phenotype of two TNBC cell line variants, by assessing their energy synthesising pathways. Profiling of the miRNA content of plasma from obese and MetS participants in an intervention study identified miR-758-3p as a potential diagnostic biomarker for MetS independent of obesity. This miRNA was also shown to have potential as a biomarker for response to dietary intervention with whey protein, as there was a positive clinical outcome for participants randomised to the whey dietary group following a high fat meal. Studies of extracellular vesicles (EV) secreted from healthy control, obese and MetS participants revealed that EV quantities may be used to diagnose MetS, independent of obesity, as EV quantities from MetS participants were found to be significantly higher than the quantities of healthy controls and obese participants.
Keywords: Pharmacy & Phamaceutical Sciences, Ph.D.; PhD Trinity College Dublin, 2017